Effect of minerals on the stability of biochar. (August 2018) - Yang, Yan; Sun, Ke; Han, Lanfang; Jin, Jie; Sun, Haoran; Yang, Yu; Xing, Baoshan
Abstract: The stability of biochar is a major determinant of its potential for carbon sequestration. In previous studies, the biochar stability was evaluated by analyzing the oxidation resistance property of biochar, for which, K2 Cr2 O7 /H2 O2 oxidation and thermogravimetric analysis (TGA) were widely used to measure the high oxidation resistance of biochars. In this study, rice straw (RI)- and swine manure (SW)-derived biochars produced at different heating treatment temperatures (HTTs) and their corresponding de-ashed biochars and iron-biochars were selected to investigate the effect of minerals on these biochars stability. There was a significantly positive correlation between carbon remaining values (CRVs) obtained after K2 Cr2 O7 /H2 O2 oxidation and ash (mineral) contents of biochars ( p < 0.05). Moreover, the decreasing CRVs of most biochars were observed after de-ashing treatment. These K2 Cr2 O7 /H2 O2 oxidation results indicated that endogenous minerals in biochars can protect biochars from chemical oxidation. On the other hand, the R 50 (C recalcitrance index) values of iron-biochars (33.3–57.4%) were lower than those of corresponding biochars (38.6–60.8%), indicating that Fe-bearing mineral formed in biochars can promote the thermal decomposition of biochars. In H2 O2 oxidation, the different change trend of CRVs between biochars produced at 450 °C and biochars produced at 600 °C after iron mineral treatment showed that the effect of exogenous Fe-bearing mineral on biochar stability was related to biochar category regulated by HTTs. This study indicated that endogenous minerals could increase biochar stability, and exogenous Fe-bearing minerals had dissimilar effects on different kinds of biochars, which critically regulates the potential of biochar for long-term carbon sequestration. Graphical abstract: Image 1 Highlights: Biochar stability was evaluated by determining its oxidation resistance. Endogenous mineral in biochar can protect biochar against chemical oxidation. Effect of exogenous mineral on biochar stability depended on biochar category.